THE INFLUENCE OF LITERACY AND NUMERACY SKILLS ON THE SUCCESS OF COLLEGE STUDENTS IN THE FACULTY OF TEACHER TRAINING AND EDUCATION - Sebastianus Widanarto Prijowuntato; Bonifasius Widharyanto; Hongki Julie (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2022)
In Indonesia, there are still many 3T zones, it defined as marginal, border, and isolated areas that require special development. College students from 3T zones are more likely to struggle with literacy and numeracy skills. Literacy and numeracy skills are, in fact, one of the success variables for students when they graduate and begin their careers. Literacy and numeracy skills are essential to learning, even university students, to receive learning effectively. The objective of this research is to examine the effect of literacy and numeracy skills on the success of students in higher education based on their GPA, particularly students from the 3T zone. The sample in this study were 57 students of Teachers Training and Education Faculty, Sanata Dharma University. Data were analyzed using simple regression. The results showed that numeracy skills have a positive and significant effect on student GPA but in the weak category with R=0.278. The regression equation Y= 2.429 + 0.033X. Literacy skills have a positive and significant effect on GPA but in moderate category with R=0.488. The regression equation for this effect is Y = 1.911 + 0.076X. Further research should be conducted to investigate not only the mastery of literacy and numeracy skills and their influences on GPA, but also their effect on employability skills.